Applying AHP to Select the Best Vendor for Bio-Efficacy Trials - Astriani, Maria; Siallagan, Manahan P (Jurnal Bisnis dan Pemasaran Digital, 2024)
Purpose: The pesticide industry is highly regulated by various regulations and requirements. Getting a distribution permit for a pesticide depends on the results of bio-efficacy trials carried out by institutions outside the company (vendors). These vendors must be selected from a list that has been made by the Ministry of Agriculture. Choosing a vendor is quite a difficult endeavor because not all vendors have the same competencies. Research Methodology: One method to choose a vendor among several vendors based on various criteria hierarchically that meets the requirements is to use the Analytical Hierarchy Process (AHP) method. This thesis presents the results of the trial of the use of the AHP method in the XYZ Agrochemical Company using a qualitative and quantitative approach by collecting primary data through questionnaires and interviews with a team of Research and Development experts from the XYZ Agrochemical Company. Results: The results of the case study at the XYZ Agrochemical Company show the practical application of the AHP model in real-world vendor selection scenarios, providing an overview of the relative significance of each criterion and its impact on the overall decision-making process. Conclusions: The study concludes that the use of the Analytical Hierarchy Process (AHP) method effectively supports the R&D team of the XYZ Agrochemical Company in determining and prioritizing the selection criteria and sub-criteria for qualified bio-efficacy trial vendors. Applying the AHP method to four vendors allowed for an objective ranking based on agreed-upon parameters, ensuring a transparent and data-driven vendor selection process. This approach enhances decision-making in selecting the most suitable vendor to support regulatory compliance and product development goals. Limitations: Secondary data was obtained from government regulations, company reports, and relevant literature to form vendor profiles, organizational capabilities, and pesticide regulations that apply specifically to Indonesia. Contribution: Through the AHP framework, based on the results of the interview, a hierarchical structure of evaluation criteria in selecting vendors was established, including expertise, past performance, laboratory and field facilities, timely delivery, in conducting bio-efficacy trials, and vendor responsiveness in communicating.